2018
DOI: 10.1016/j.amjmed.2018.07.028
|View full text |Cite
|
Sign up to set email alerts
|

Career-Focused Mentoring for Early-Career Clinician Educators in Academic General Internal Medicine

Abstract: AAIM is the largest academically focused specialty organization representing departments of internal medicine at medical schools and teaching hospitals in the United States and Canada. As a consortium of five organizations, AAIM represents department chairs and chiefs; clerkship, residency, and fellowship program directors; division chiefs; and academic and business administrators as well as other faculty and staff in departments of internal medicine and their divisions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 16 publications
0
13
0
Order By: Relevance
“…Abedin et al (2013) found that of the 55 Academic Health Centres surveyed, 96% provided mentor training at a program level and 93% at an institutional level. The general goals of the programs were to train and support mentors [2,[6][7][8][9][10][11]13,15,17,30,[48][49][50][51]70,77,81,82,86,95,106,107] and ensure a consistent mentoring experience for mentees [108,109]. McCulloch et al (2015) and Rhodes (2013) found that mentor training programs also motivate mentors.…”
Section: Structure Of Mentor-training Programmentioning
confidence: 99%
See 1 more Smart Citation
“…Abedin et al (2013) found that of the 55 Academic Health Centres surveyed, 96% provided mentor training at a program level and 93% at an institutional level. The general goals of the programs were to train and support mentors [2,[6][7][8][9][10][11]13,15,17,30,[48][49][50][51]70,77,81,82,86,95,106,107] and ensure a consistent mentoring experience for mentees [108,109]. McCulloch et al (2015) and Rhodes (2013) found that mentor training programs also motivate mentors.…”
Section: Structure Of Mentor-training Programmentioning
confidence: 99%
“…Novice mentoring dominates the mentoring landscape in medical education [1][2][3][4][5][6] and has been found to enhance innovation and career progression [7][8][9][10][11][12][13][14][15], encourage research involvement amongst women and underrepresented ethnic minorities, boost grant success [16], and publications [10,[17][18][19][20][21][22][23] and navigating the complex landscape of academic life [2,[24][25][26][27]. Clinicians who have been mentored are also more motivated, resilient, have well-developed professional identities and feel better supported in their jobs than colleagues without mentors [28][29][30][31].…”
Section: Introductionmentioning
confidence: 99%
“…12,28,29 Mentors influence mentees' scholarship productivity, retention, career satisfaction, and development as a leader and educator. 13,[30][31][32][33] In our study, mentors and role models also created a community supportive of medical education. Mentors allowed interested faculty the opportunity for socialization in the field of medical education and were an introductory influence on a career as a CE.…”
Section: Discussionmentioning
confidence: 94%
“…Although some specialties, such as general internal medicine (GIM) and emergency medicine [1][2][3][4], have well-established communities and pathways for clinician-educators, others have only recently recognized the needs of their clinician-educator members. Often, the predominant career pathways for academic internal medicine (IM) subspecialties are based on basic science or clinical/translational research models.…”
Section: Introductionmentioning
confidence: 99%